PENINGKATAN KOMPETENSI GURU BIDANG KEAHLIAN BISNIS MANAJEMEN MELALUI PENELITIAN TINDAKAN KELAS - Raya Sulistyowati; Siti Sri Wulandari; Bambang Suratman (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2018)
the purpose of this activity is to meet the needs of teachers in improving teacher competence in the field of business management expertise of teachers in SMKN 1 and SMK Ketintang Surabaya. The reason for doing this classroom action research training (1) to make teachers sensitive and responsive to the dynamics of learning in its class. (2) Improving teachers' performance to become professionals (3) teachers improves the learning process through an in-depth assessment of what is happening in their classroom. (4) classroom action research does not interfere with a teacher's main task because the teacher does not need to leave the class. The results of these activities in the form of articles of scientific work of classroom action research used by teachers as material for improving the process and the results of student learning in the classroom. It is expected that through the classroom action research training and the accompaniment of the script writing of the classroom action research results. And ultimately teachers SMKN Surabaya and SMK Ketintang Surabaya Business Management can improve scientific publications and can increase functional allowance and teacher credit numbers in developing teacher careers.